Chuck Klosterman X : a highly specific, defiantly incomplete history of the early 21st century. - Klosterman, Chuck, 1972- (Blue Rider Press, 2017)
"New York Times-bestselling author and cultural critic Chuck Klosterman compiles and contextualizes the best of his articles and essays from the past decade. Chuck Klosterman has created an incomparable body of work in books, magazines, newspapers, and on the Web. His writing spans the realms of culture and sports, while also addressing interpersonal issues, social quandaries, and ethical boundaries. Klosterman has written nine previous books, helped found and establish Grantland, served as the New York Times Magazine Ethicist, worked on film and television productions, and contributed profiles and essays to outlets such asGQ, Esquire, Billboard, The A.V. Club, and The Guardian. Chuck Klosterman's tenth book (aka Chuck Klosterman X) collects his most intriguing of those pieces, accompanied by fresh introductions and new footnotes throughout. Klosterman presents many of the articles in their original form, featuring previously unpublished passages and digressions. Subjects include Breaking Bad, Lou Reed, zombies, KISS, Jimmy Page, Stephen Malkmus, steroids, Mountain Dew, Chinese Democracy, The Beatles, Jonathan Franzen, Taylor Swift, Tim Tebow, Kobe Bryant, Usain Bolt, Eddie Van Halen, Charlie Brown, the Cleveland Browns, and many more cultural figures and pop phenomena. This is a tour of the past decade from one of the sharpest and most prolific observers of our unusual times"--